D-最优混料设计优化速冻专用油脂乳化剂配方Optimization of emulsifier formula of fast-frozen special fat by D-optimum mixture design - 朱利萍1，孙聪1,2，李开放2，张顺昌2，梁少华1，杨国龙1，刘伟1 ZHU Liping1, SUN Cong1,2, LI Kaifang2, ZHANG Shunchang2, LIANG Shaohua1, YANG Guolong1, LIU Wei1 (Zhongguo youzhi, 2023)
为解决速冻食品易开裂的问题，对速冻专用油脂乳化剂配方进行设计优化。首先以自制酯交换油脂为基料油，以吸水性和乳化稳定性为指标，对6种常用的亲油性乳化剂进行筛选，并采用D-最优混料设计确定最佳乳化剂配方，然后用该乳化剂配方制备速冻专用油脂，并将自制速冻专用油脂和两种市售速冻专用油脂制作速冻汤圆作应用对比试验。结果表明：以酯交换油脂为基料油的速冻专用油脂最佳乳化剂配方为硬脂酰乳酸钙添加量34.4%、单硬脂酸甘油酯添加量338%、大豆卵磷脂添加量31.8%，在此条件下复合乳化剂的吸水性为25.1 mL/10 g，乳化稳定性为933%；相比于市售速冻专用油脂，自制速冻专用油脂制作的速冻汤圆表面光滑、裂纹少，冻裂率和冷冻失水率低。因此，优化得到的速冻专用油脂复合乳化剂具备良好的乳化稳定性和持水能力，可降低速冻食品的冻裂率。In order to solve the cracking problem of fast-frozen food, the emulsifier formula of fast-frozen special fat was optimized. With water absorption and emulsifying stability as indexes, using self-made transesterification oil as base oil, six commonly used lipophilic emulsifiers were selected, and the best emulsifier formula was determined by D-optimum mixture design. In addition, the application of self-made fast-frozen special fat and two kinds of commercial fast-frozen special fat to produce fast-frozen dumpling was compared. The results showed that with self-made transesterification oil as base oil, the optimal emulsifier formula for fast-frozen special fat was obtained as follows: dosage of calcium stearoyl lactylate 34.4%, dosage of glycerol monostearate 33.8%, and dosage of soybean lecithin 318%. Under these conditions, the water absorption and emulsifying stability of compound emulsifier were 25.1 mL/10 g and 93.3%, respectively. Compared with the commercial fast-frozen special fat, the fast-frozen dumpling made by the self-made fast-frozen special fat had a smooth surface, fewer cracks, lower freeze-cracking rate and freezing water loss rate. The optimized compound emulsifier has good emulsifying stability and water-holding capacity, and can reduce the freeze-cracking rate of fast-frozen food.